Phytochemical Evaluation, Physicochemical Standardization, and Antioxidant Potential of a Polyherbal Formulation: A Comprehensive Assessment - Yadav, Garima; Arora, Isha; Rani, Pooja; Nandal, Rimmy (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation, standardization, and evaluation of a traditional polyherbal churna comprising Zingiber officinale, Piper nigrum, Plumbago zeylanica, Terminalia chebula, Trachyspermum ammi, and Argyreia nervosa. The formulation was prepared in-house following classical Ayurvedic guidelines, and its quality was assessed through organoleptic, physicochemical, and phytochemical parameters. Physicochemical parameters such as foreign organic matter, loss on drying, ash values, and extractive values of individual ingredients were found within pharmacopoeial limits, ensuring purity and consistency. Organoleptic analysis showed a light brown powder with pungent taste and characteristic odour. The formulation demonstrated acceptable flow properties with bulk and tap densities of 0.382 and 0.462 g/ml, respectively. The sodium content was 8.5 ppm, and the pH ranged from neutral to mildly acidic (7.05 and 5.60 for 1% and 10% w/w, respectively). Phytochemical screening revealed a total phenolic content of 188 µg/ml, tannin content of 12%, piperine content of 0.552%, and gallic acid content of 0.382%. Antioxidant activity evaluated by DPPH, total antioxidant capacity, and reducing power assays revealed strong free radical scavenging potential, especially in methanolic extract, with IC50 values of 98 µg/ml (DPPH). The results validate the antioxidant efficacy and traditional therapeutic relevance of the polyherbal formulation, supporting its future use in clinical or preventive herbal applications.